Drivers of Secondary School Students' Intention to Enroll in Science Studies - Nordin, Mohamad Sahari; Tunku Ahmad, Tunku Badariah; Ibrahim, Mohd Burhan; Abu Libdeh, Enas Saied (Horizon Research Publishing Corporation, 2019)
This paper reports on a survey conducted in selected secondary schools in Malaysia to explore students' intention to enroll in science studies and establish whether intention would be influenced by attitude towards science, science-efficacy, subjective norm, and perceived difficulty of science subjects. Another aim of the survey was to determine if gender, ethnicity, and school location moderated the associations between intention and its predictors. The data were collected randomly from 398 15-year-old students from 38 secondary schools in Malaysia using a 15-item questionnaire. To address the research objectives, the data were analyzed with confirmatory factor analysis and structural equation modeling. The results supported the hypotheses that the four predictors were adequate to explain intention to pursue science studies, particularly attitude and science-efficacy which were the most influential predictors. Additionally, gender, ethnicity, and school location did not moderate the predictor-intention relationships. The results suggest that the planning, implementation and evaluation of efforts to enhance science participation among students should consider how to develop more science-efficacy and positive attitudes towards the subjects.